A Framework for Detecting and Preventing Double Spent Data in Inter and Intra Block of Blockchain - J. , Vijayalakshmi; A., Murugan (International Journal of Psychosocial Rehabilitation, 2020)
Optimistically, our global economy moves towards the digital eco-system. Everything is going to be paperless communication, from investment to money transfer. The newest and most assured digital payment sector is cryptocurrency. A cryptocurrency is a digital currency that uses cryptography as a medium of exchange like normal currencies. Bitcoin was the first decentralized cryptocurrency, which has properties like supporting privacy, security, fast and cost-effective transactions, transparency, and immutability. Bitcoin is still dominant over 2000 cryptocurrencies. Double spending is the main issue faced by the Bitcoin network. Double spending is the method in which the same digital currency is spent multiple times by creating duplicate transactions. This issue needs to be resolved to make sure that it is not being abused and that it maintains its value and trust. This paper has proposed several techniques for identifying and preventing double-spent transactions in both inter- and intra-block communication of the Bitcoin blockchain network.